Contributions of phenolics and added vitamin C to the antioxidant capacity of pomegranate and grape juices: synergism and antagonism among constituents. (22nd July 2013) - Bolling, Bradley W.; Chen, Ya‐Yen; Chen, C‐Y. Oliver
Summary: The aim of this study was to examine the contribution of sugar, organic acid, neutral phenol, and anthocyanin fractions and added ascorbic acid to grape and pomegranate‐nectarine juice total phenol, oxygen radical absorbance capacity (ORAC), ferric reducing antioxidant power (FRAP) and 2, 2‐diphenyl‐1‐picrylhydrazyl (DPPH) values. Neutral phenol and anthocyanin fractions contributed ≥75% of the total antioxidant capacity (TAC) for both juices. Intrinsic synergy and antagonism among the fractionated constituents occurred inconsistently in each assay. Sugars and organic acids antagonised pomegranate juice neutral phenols and anthocyanins in the DPPH assay by 50% and the grape juice ORAC value by 21%, but were synergistic to the grape juice FRAP value. The added ascorbic acid was dose‐dependently synergistic with pomegranate and grape juice total phenol, DPPH and FRAP assays, but less so in the ORAC assay. Thus, the interactions between grape and pomegranate juice constituents determine TAC and total phenol values, and synergy in these assays could not be attributed solely to polyphenols.